Adverse Effect of Nonylphenol on the Reproductive System in F2 Male Mice : A Qualitative Change? - Kim, Yong-Bin; Cheon, Yong-Pil; Choi, Donchan; Lee, Sung-Ho (Balsaeng'gwa saengsig, 2019)
Previously, we reported negative effects of low-dose nonylphenol (NP) exposure on the reproductive organs of F1 male mice. In the present study was further investigated the endocrine disrupting effect of NP exposure to F2 generation male mice. Mice were divided into 2 groups; (1) CON, control animals and (2) NP-50 (50 μg/L), animals were treated with NP via drinking water. NP exposures were continuously conducted from parental pre-mating period until the postnatal day (PND) 55 of F2 offsprings. Mice were sacrificed on PND 55 and the reproductive tissue weights were measured. The initial (at PND 21) and terminal (PND 55) body weights of the NP-50 group animals were not significantly different from those of control group animals. NP exposure fail to induce a significant weight change of the testes, seminal vesicle and prostate except absolute epididymal weight (p<0.05). However, pathohistological studies revealed that NP-treated F2 animals showed evident decrease in seminiferous tubule diameters, reduced luminal area and number of germ cells. Also, sloughing morphologies in the tubules were notable. In the caudal epididymis, fewer mature sperms and swollen epithelial cells were found in the NP-treated group. The present study demonstrated that the subchronic low-dose NP exposure induced pathohistological abnormalities in testis and epididymis of F2 mice, and we assumed that these 'qualitative' changes in reproductive tissues could be derived from the epigenetic modifications such as DNA methylation, histone modification, altered DNA accessibility and chromatin structure. Further studies are needed to achieve a better understanding on the multi- or trans-generational effects of NP on the reproductive health and a human application.Previously, we reported negative effects of low-dose nonylphenol (NP) exposure on the reproductive organs of F1 male mice. In the present study was further investigated the endocrine disrupting effect of NP exposure to F2 generation male mice. Mice were divided into 2 groups; (1) CON, control animals and (2) NP-50 (50 μg/L), animals were treated with NP via drinking water. NP exposures were continuously conducted from parental pre-mating period until the postnatal day (PND) 55 of F2 offsprings. Mice were sacrificed on PND 55 and the reproductive tissue weights were measured. The initial (at PND 21) and terminal (PND 55) body weights of the NP-50 group animals were not significantly different from those of control group animals. NP exposure fail to induce a significant weight change of the testes, seminal vesicle and prostate except absolute epididymal weight (p<0.05). However, pathohistological studies revealed that NP-treated F2 animals showed evident decrease in seminiferous tubule diameters, reduced luminal area and number of germ cells. Also, sloughing morphologies in the tubules were notable. In the caudal epididymis, fewer mature sperms and swollen epithelial cells were found in the NP-treated group. The present study demonstrated that the subchronic low-dose NP exposure induced pathohistological abnormalities in testis and epididymis of F2 mice, and we assumed that these 'qualitative' changes in reproductive tissues could be derived from the epigenetic modifications such as DNA methylation, histone modification, altered DNA accessibility and chromatin structure. Further studies are needed to achieve a better understanding on the multi- or trans-generational effects of NP on the reproductive health and a human application.